Durability study on alumino-silicate concrete, synthesized using anthracite coal fly ash - Kannapiran; Sujatha; Nagan (Journal of Structural Engineering, 2024)
Ever since our ancestors constructed dwellings, mortars such as mud, red earth, lime, cement, etc., played a vital role as binders. Of late, it is found that production of cement contributes significantly to emission ofCO₂ and the quantum of CO₂ is manifold and uncontrollable. This phenomenon has forced scientists to invent an alternative binding material to cement. Geopolymer, a member of inorganic family, has been identified as a suitable substitute to cement and it is totally a noncementitious binder.However, it has to be tested for its durability and serviceability so that it can be promoted globally. Fly ash, a by-product produced by industries can be used as a feedstock for geopolymer. Variations in the ratio of aluminum to silicon in Indian fly ash, and alkali to silicon, produce geopolymers with different physical and mechanical properties. This paper describes the durability of heat- cured “low-calcium fly-ash-based geopolymer concrete”. The experimental work involves durability tests which are currently available for OPC as per ASTM standards on low-calcium Indian fly-ash-based geopolymer concrete. It has excellent compressive strength, suffers very little drying shrinkage, excellent resistance to sulphate attack, and good acid resistance. The geopolymer concrete is heat cured at 70 ◦C. This paper effectively implies the variations of M30 and M50 grade of concrete with NaOH molarity as 14M.